2010
DOI: 10.3310/hta14150
|View full text |Cite
|
Sign up to set email alerts
|

A randomised controlled multicentre trial of treatments for adolescent anorexia nervosa including assessment of cost-effectiveness and patient acceptability – the TOuCAN trial

Abstract: NRR number (National Research Register) N0484056615; Current Controlled Trials ISRCTN39345394.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
104
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(110 citation statements)
references
References 191 publications
3
104
0
3
Order By: Relevance
“…Descriptive data for the 71 60,70,71,92,115-117, 120,134,136 There were relatively few studies focusing on post-traumatic stress disorder (PTSD) (n = 2), 86,128 self-harm (n = 4) 72,74,78,137 and generic mental health problems (i.e. interventions designed for any mental health problem; n = 3).…”
Section: Description Of the Included Effectiveness Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Descriptive data for the 71 60,70,71,92,115-117, 120,134,136 There were relatively few studies focusing on post-traumatic stress disorder (PTSD) (n = 2), 86,128 self-harm (n = 4) 72,74,78,137 and generic mental health problems (i.e. interventions designed for any mental health problem; n = 3).…”
Section: Description Of the Included Effectiveness Studiesmentioning
confidence: 99%
“…51,107,133 There were no studies on psychosis. Most (31/71) of the studies concerned interventions that could be classified as treatments (see Chapter 1, Intervention levels), [48][49][50][51][52]55,65,66,70,71,74,77,78,81,[83][84][85][86]91,[94][95][96][97][98][101][102][103][104]106,111,112,[121][122][123][124][125][126][127][129][130][131]133,135,139 with the remainder focusing equally on indicated (n = 11), 53,58,59,…”
Section: Description Of the Included Effectiveness Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Ausführliche Beschreibungen der erforderlichen somatischen Massnahmen beim Ernährungs-aufbau bei schwerer Anorexia nervosa sowie das Management der somatischen Komplikationen bei Bulimia nervosa finden sich bei Mehler et al [71,72] spätere Behandlungen entscheidend verschlechtern kann. Studien konnten die Überlegenheit von stationären Behandlungen gegenüber ambulanten Settings nicht nachweisen [73,74]. Die Möglichkeiten für teilstationäre Behandlungen sind bis heute in der Schweiz noch begrenzt.…”
Section: Management Somatischer Komplikationenunclassified
“…354,372 This compared the costs and outcomes of inpatient treatment, specialist outpatient treatment and TAU and found that specialist outpatient treatment had a higher probability of being cost-effective (up to approximately 60%). One limitation of this study was that only 65% of patients adhered to the allocated treatment.…”
mentioning
confidence: 99%